Probing the Modulation of Acute Ethanol Intoxication by Pharmacological Manipulation of the NMDAR Glycine Co‐Agonist Site. (30th August 2012) - DeBrouse, Lauren; Hurd, Benita; Kiselycznyk, Carly; Plitt, Aaron; Todaro, Alyssa; Mishina, Masayoshi; Grant, Seth G. N.; Camp, Marguerite; Gunduz‐Cinar, Ozge; Holmes, Andrew
<x xml:space="preserve">Abstract</x> Background Stimulating the glycineB binding site on the N‐methyl‐d‐aspartate ionotropic glutamate receptor (NMDAR) has been proposed as a novel mechanism for modulating behavioral effects of ethanol (EtOH) that are mediated via the NMDAR, including acute intoxication. Here, we pharmacologically interrogated this hypothesis in mice. Methods Effects of systemic injection of the glycineB agonist, d‐serine, the GlyT‐1 glycine transporter inhibitor, ALX‐5407, and the glycineB antagonist, L‐701, 324, were tested for the effects on EtOH‐induced ataxia, hypothermia, and loss of righting reflex (LORR) duration in C57BL/6J (B6) and 129S1/SvImJ (S1) inbred mice. Effects of the glycineB partial agonist, d‐cycloserine (DCS), the GlyT‐1 inhibitor, N‐[3‐(4′‐fluorophenyl)‐3‐(4′‐phenylphenoxy)propyl]sarcosine (NFPS), and the glycineB antagonist, 5, 7‐dichlorokynurenic (DCKA), on EtOH‐induced LORR duration were also tested. Interaction effects on EtOH‐induced LORR duration were examined via combined treatment with d‐serine and ALX‐5407, d‐serine and MK‐801, d‐serine and L‐701, 324, as well as L‐701, 324 and ALX‐5407, in B6 mice, and d‐serine in GluN2A and PSD‐95 knockout mice. The effect of dietary depletion of magnesium (Mg), an element that interacts with the glycineB site, was also tested. Results Neither d‐serine, DCS, ALX‐5407, nor NFPS significantly affected EtOH intoxication on any of the measures or strains studied. L‐701, 324, but not DCKA, dose‐dependently potentiated the ataxia‐inducing effects of EtOH and increased EtOH‐induced (but not pentobarbital‐induced) LORR duration. d‐serine did not have interactive effects on EtOH‐induced LORR duration when combined with ALX‐5407. The EtOH‐potentiating effects of L‐701, 324, but not MK‐801, on LORR duration were prevented by d‐serine, but not ALX‐5407. Mg depletion potentiated LORR duration in B6 mice and was lethal in a large proportion of S1 mice. Conclusions GlycineB site activation failed to produce the hypothesized reduction in EtOH intoxication across a range of measures and genetic strains, but blockade of the glycineB site potentiated EtOH intoxication. These data suggest endogenous activity at the glycineB opposes EtOH intoxication, but it may be difficult to pharmacologically augment this action, at least in nondependent subjects, perhaps because of physiological saturation of the glycineB site.